A Review of the Underlying Constructs of Connectedness to Nature among Children - Mustapa, Nor Diyana; Maliki, Nor Zarifah; Aziz, Nor Fadzila; Hamzah, Aswati (Universiti Sains Malaysia, 2016)
A strong connectedness to nature that developed during childhood forms a basis for human to have a positive attitude and behaviour towards nature in adulthood later. Acknowledging the importance of connectedness to nature during childhood, environmental psychologists have introduced various concepts of connectedness to nature, and various instruments have been employed to measure the concept. However, the underlying constructs to measure connectedness to nature among children seem unclear. Hence, it is worth to formulate a proper understanding on the underlying constructs of children’s connectedness to nature. Based on a systematic review, this paper aims to delineate the constructs of connectedness to nature referring to the existing adult and children instruments. Issues pertaining to connectedness to nature conceptualization and uni-dimensional versus multi-dimensional also will be discussed. This paper further suggests the direction for future research.